QUALITATIVE RESEARCH OF PLACEBO EFFECT ON MARKETING TOWARD PRODUCT PRICING - Pilat, Viddie Johnpietra (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Placebo effect recently gain much attention from the side of marketing researcher strive to deepen their knowledge about the influence of various psychological concept on consumer behavior.Â  It is well know that manipulating with various marketing variable (e.g. price change, packaging, distribution channels) can significantly influence the customer believe and expectation and hence change their perceptions of a product. This research is designed to have a clearer image and deeper understanding about the the placebo effect on price among the consumer. The method used in this research is the qualitative research methodology with case study research approach which will provide a descriptive insight about the placebo effect. The data for this research were gathered from observation,interviews and documents, which the sample is random people with different ocupation to get an impulsive idea about the placebo effect.In the findings, there are several perspective about the placebo effect on price but the main point is placebo effect is the fundamental to determine the quality of the product. Never underestimate the power of mind over matter. Payment might change level of abilities and skills. True or not, pay customers what it is worth, not the lowest that can get away with, because itâ€™s the right thing to do. Keywords: placebo effect, product, price